2020
DOI: 10.1038/s41598-020-62844-9
|View full text |Cite
|
Sign up to set email alerts
|

Connexin-43 reduction prevents muscle defects in a mouse model of manifesting Duchenne muscular dystrophy female carriers

Abstract: Duchenne muscular dystrophy (DMD) is a severe X-linked neuromuscular disorder that affects males. However, 8% of female carriers are symptomatic and underrepresented in research due to the lack of animal models. We generated a symptomatic mouse model of DMD carriers via injection of mdx (murine DMD) embryonic stem cells (ESCs) into wild-type (WT) blastocysts (mdx/WT chimera). mdx/WT chimeras developed cardiomyopathic features and dystrophic skeletal muscle phenotypes including elevated mononuclear invasion, ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 60 publications
2
12
0
Order By: Relevance
“…After detecting Cx43, which affects myocardial electrical conduction and contraction, we only found a decrease in its abundance, but no apparent abnormal subcellular localization. As previously reported, the reduction of Cx43 in muscles could prevent and protect myocardial and skeletal muscle damage during muscular dystrophy 48,49 . We believe that the decrease of Cx43 in myomesin‐1‐deficient cardiomyocytes is a protective mechanism to prevent the damage of myocardial atrophy caused by myomesin‐1 deficiency.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…After detecting Cx43, which affects myocardial electrical conduction and contraction, we only found a decrease in its abundance, but no apparent abnormal subcellular localization. As previously reported, the reduction of Cx43 in muscles could prevent and protect myocardial and skeletal muscle damage during muscular dystrophy 48,49 . We believe that the decrease of Cx43 in myomesin‐1‐deficient cardiomyocytes is a protective mechanism to prevent the damage of myocardial atrophy caused by myomesin‐1 deficiency.…”
Section: Discussionsupporting
confidence: 71%
“…were increased in KO CMs relative to WT CMs, their absolute expression was still at a low level and there was still no M-line in As previously reported, the reduction of Cx43 in muscles could prevent and protect myocardial and skeletal muscle damage during muscular dystrophy. 48,49 We believe that the decrease of reported that intact myomesin-1 and its specific Fn-like or Iglike domains can stimulate human myoblast proliferation. 37 To investigate the effect of MYOM1 knockout on the number of cardiomyocytes, we next tested the proliferation and apoptosis of cardiomyocytes.…”
Section: Discussionmentioning
confidence: 98%
“…The links between Gcn5 Skm-/and muscular disease were further emphasized by observed negative correlations between the Gcn5 Skm-/bioset and that of KO mice for Mstn, Cx43 and Mir-21, genes that have been linked to playing a negative role on mdx mouse phenotypes (Fig. 3c) (Nouet et al, 2020;Zanotti et al, 2015;Ardite et al, 2012;Dumonceaux et al, 2010). The finding that the Gcn5 Skm-/bioset is negatively correlated with several Mstn KO biosets compliments findings that suggest myostatin pathway inhibition as a potential DMD therapeutic strategy (Campbell et al, 2017).…”
Section: Discussionmentioning
confidence: 92%
“…The role of connexins (Cxs), particularly of Cx43, in different cardiomyopathies, including DMD-associated cardiomyopathies, is well established. Less is known regarding the role of Cx43 and other connexins in skeletal muscle [ 106 ].…”
Section: Other Regulators Of P2x7r Signalingmentioning
confidence: 99%
“…Interestingly, in their study, they unveil that Cx43 is not expressed by wt or dystrophinopathic muscle fibers but rather by infiltrating F4/80 + mononuclear cells. Cx43 gene inactivation improved histological features of muscular dystrophy in mdx /chimera mice suggesting that the development of anti-Cx43 therapies could be beneficial to ameliorate inflammation in DMD [ 106 ].…”
Section: Other Regulators Of P2x7r Signalingmentioning
confidence: 99%